The dynamics of income inequality: the case of China in a comparative perspective - Chan, T; Ermisch, J; Gruijters, R (Oxford University Press, 2019)
We compare household income panel data from China, Germany, the United Kingdom, and the United States. Consistent with previous research, we show that income is more unequally distributed in China than in the three Western countries. But China also has a higher level of intra-generational income mobility. Because mobility tends to have an income-equalizing effect, the snapshot measures of inequality overstate the true level of inequality in China to a greater degree than they do for the other countries. But even after we have taken into account the impact of mobility, permanent income is still more unequally distributed in China than in the United States, the United Kingdom, and Germany. Moreover, in the three Western countries, the lion’s share of income inequality is between individuals rather than within individual. The opposite holds for China. We also show that the most important determinants of income inequality in China are those long-standing institutions that predate the market reform.